Investigation of harvesting energy vibrations due to the feed process on milling machines - Andi Suryadi; Subekti Subekti; Nur Indah (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
Milling machines are machines used in the production process. The time required during the machining process must be more efficient in order to obtain the desired production capacity. The aim of this paper is to utilize vibrations originating from milling machines in industry as a source of Harvesting Energy Vibration. The research was carried out by varying the feeding depth of the milling machine so that it could be seen how much stress was produced. The Lushan Model ZX32 milling machine was used in this research, where vibrations from the vibration source were measured using an FFT Analyzer connected to an Accelerometer Sensor and Harvesting energy vibration connected to an Oscilloscope. Meanwhile, the workpieces used in this research were Aluminum 5052 and PVC. The results of the research were that on PVC material with an ingestion depth of 1 mm, the vibration frequency at 210 rpm was 71 Hz, the amplitude was 1.38 mm/s2, resulting in a harvesting energy of 6.449 mV. And the results of research using aluminum at 210 rpm rotation with a feeding depth of 3 mm obtained a vibration frequency of 90 Hz with an amplitude of 1.508 mm/s2 producing a harvesting energy of 5.856 mV. The research results show that the PVC material produces higher harvesting energy vibration at a depth of 1 mm, and the aluminum material produces higher harvesting energy vibration at a depth of 3 mm